Răspuns :
Răspuns:
[tex]\boldsymbol {\red{S = {(-9;2);(2;-9);(1;2);(2;1)}}}[/tex]
Explicație pas cu pas:
Notăm x+y = s și xy = p
[tex]\begin{cases}s^2 + 2p = 13\\2s - p = 4 \ \ |\cdot2\end{cases} \Rightarrow \begin{cases}s^2 + 2p = 13\\4s - 2p = 8\end{cases}[/tex]
s² + 4s = 21
(s + 7)(s - 3) = 0
s = -7; s = 3
Aflăm p:
s = -7 ⇒ p = 2(-7) - 4 ⇒ p = -18
s = 3 ⇒ p = 2•3 - 4 ⇒ p = 2
Revenim la notație:
[tex]\begin{cases}x + y = -7 \\ xy = -18\end{cases} \Rightarrow \begin{cases}y = -x-7 \\ x (-x-7) = -18\end{cases} \Rightarrow \begin{cases}y = -x-7 \\ x^2 + 7x -18 = 0\end{cases} \Rightarrow\begin{cases}y = -x-7 \\ (x + 9)(x - 2)\end{cases}[/tex]
x = -9 ⇒ y = -(-9) - 7 = 9 - 7 = 2
x = 2 ⇒ y = - 2 - 7 = -9
[tex]\begin{cases}x + y = 3 \\ xy = 2\end{cases} \Rightarrow \begin{cases}y = 3 - x \\ x(3 - x) = 2\end{cases} \Rightarrow \begin{cases}y = 3 - x \\ x^2 - 3x + 2 = 0\end{cases} \Rightarrow \begin{cases}y = 3 - x \\ (x - 1)(x - 2) = 0\end{cases}[/tex]
x = 1 ⇒ y = 3 - 1 = 2
x = 2 ⇒ y = 3 - 2 = 1
Soluțiile sunt:
S = {(-9;2);(2;-9);(1;2);(2;1)}